Manajemen Pendidikan Diniyah Formal Berbasis Pondok Pesantren dalam Meningkatkan Kompetensi Santri Pondok Pesantren Minhaajurrasyiddin Jakarta Timur - Misbach, Wahyu; Fahruddin, Zuhri (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
The background of this research problem is the concern over the scarcity of ulama cadres (mutafaqqih fiddin) due to the low interest of students to enter pesantren. This is due to the public perception that education in pesantren cannot continue to a higher level of education. The Ministry of Religious Affairs responded to this problem by opening Formal Early Childhood Education (PDF) in Islamic boarding schools as a constructive step in the world of education. The purpose of this study is to describe the efforts of PDF Minhajurrosyidin management to form a cadre of religious professional scholars according to the demands of the times by increasing santri competence through the Century skills model approach which is a must-have skill in 21st century competition including metacognitive skills, competitiveness skills, life and career skills, learning and innovation skills, and information, media, and technology skills. This research method uses descriptive qualitative with data collection steps through observation, interviews, and documentation. Data analysis applies Triangulation of natural field research data so that the results can be trusted. The result of this research is that PDF management implements a clerking pattern as a hotline between students and all parties. The guardianship pattern is also a supervisor of santri activities at school and at the boarding school. PDF management effectively uses a scientific approach that refers to the realm of cognitive, affective, and skill competencies. This increases the interest of students to enter the pesantren because it has been proven that PDF Minhaajurrasyiddin East Jakarta graduates get the legality to continue to the formal education level.